ANALISIS PENGARUH BRAND EQUITY DAN FAKTOR RELIGIUSITAS TERHADAPKEPUTUSAN NASABAH DALAM MEMILIH LAYANAN JASADI BANK 9 JAMBI SYARIAH TANJUNG JABUNG TIMUR - Puspitasari, Riska (Jurnal Literasiologi, 2024)
Low sharia financial literacy will affect the use and utilization of sharia financial services which will lead to market share, especially sharia banking. It is hoped that financial literacy will not only increase public knowledge, but also change people's behavior in managing finances better and being able and intelligent in choosing fake investments. In this case, I as a researcher will discuss the scope of banking at Bank 9 Jambi in Tanjung Jabung Timur, especially in terms of brand, religiosity and services in choosing a product which is the main basis for prospective customers at Islamic banks. However, there are those who use sharia banks only to pay for college administration because the lack of financial literacy in forming sharia finance requires optimizing a correct understanding of sharia finance. The attitude of religiosity which is a benchmark for consumers will make it easier to choose a product at the bank, apart from that, the products at the sharia bank will not be valid if there is a lack of literacy.